2020
DOI: 10.1038/s10038-020-00873-y
|View full text |Cite|
|
Sign up to set email alerts
|

Japanese insurers’ attitudes toward adverse selection and genetic discrimination: a questionnaire survey and interviews with employees about using genetic test results

Abstract: Since the 1990s, insurance has been the primary field focused on the social disadvantages of using genetic test results because of the concerns related to adverse selection. Although life insurance is popular in Japan, Japan does not currently have any regulations on the use of genetic information and insurers have largely kept silent for decades. To reveal insurers’ attitudes on the topic, we conducted an anonymous questionnaire survey with 100 insurance company employees and recruited nine interviewees from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…FMs had concerns about being treated unfavorably based on genetic characteristics, while there are no laws or regulations against genetic discrimination in Japan [14,15]. Several studies showed despite the implementation of The Genetic Information Nondiscrimination Act (GINA) in the US, low awareness and insufficient understanding persists [16,17]; even in a survey conducted 10 years later, the respondents answered incorrectly and indicated that they would refuse genetic testing due to fairness of discrimination in employment and insurance [18].…”
mentioning
confidence: 99%
“…FMs had concerns about being treated unfavorably based on genetic characteristics, while there are no laws or regulations against genetic discrimination in Japan [14,15]. Several studies showed despite the implementation of The Genetic Information Nondiscrimination Act (GINA) in the US, low awareness and insufficient understanding persists [16,17]; even in a survey conducted 10 years later, the respondents answered incorrectly and indicated that they would refuse genetic testing due to fairness of discrimination in employment and insurance [18].…”
mentioning
confidence: 99%
“…The recent move by the Japanese insurance industry to adopt GD guidelines is laudable, but independent monitoring and review of their implementation would provide added credibility to this initiative. A 2020 survey on the attitudes of insurance employees toward adverse selection and GD shows that it is necessary to improve understanding of GD through communication and consultation to prepare the guidelines for Japanese insurers 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we interviewed FAs and key informants to obtain their insights on the views on GD and life insurance, and the Moratorium. To our knowledge, this is the first study to conduct interviews with the financial advising sector about GD, unlike other financial industry stakeholders such as insurance companies [40][41][42].…”
Section: Permitted Behaviourmentioning
confidence: 99%
“…To understand how GD operates in Australia and ascertain the effectiveness of Australia’s current approach to regulating GD, empirical examination which captures insights from key stakeholders (e.g., consumers, health professionals, genetic researchers, and the financial industry) is required. To add to the evidence base, this article reports on the perspectives of the financial industry, specifically financial advisers (FAs), who unlike other financial industry stakeholders such as insurance companies [ 40 – 42 ], have not yet been studied, to the authors’ knowledge, in relation to underwriting in the context of genetic tests and GD.…”
Section: Introductionmentioning
confidence: 99%